Brand, Organizational Identity and Reputation in SMEs - An Overview : Qualitative Market Research - Issue 4, Volume 10. - Abimbola, Temi (Emerald Group Pub., 2007)
As we progress through the 21st century, organizations? small, medium and large - are competing in an environment that is global in nature and scope, information rich and knowledge based. In compiling this e-book, the increasing role that brand, organizational identity and reputation occupy in competitive markets loaded with meanings, and the symbols in which organizations learn to express themselves (Schultz, Hatch and Larsen, 2000). The six articles in this e-book address issues around the elements of brand, organizational identity and reputation in the context of SME. The theme that links t.